2020
DOI: 10.1111/febs.15521
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and the nicotinic cholinergic system in COVID‐19

Abstract: There is an urgent need to address the devastating pandemic, COVID‐19, caused by SARS‐CoV‐2. The efforts to understand the details of this disease in hope of providing effective treatments are commendable. It is clear now that the virus can cause far more damage in patients with comorbid conditions—particularly in those with respiratory, cardiovascular, or immune‐compromised system—than in patients without such comorbidities. Drug use can further exacerbate the condition. In this regard, the ill effects of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 96 publications
4
51
0
Order By: Relevance
“…Especially during this pandemic, cigarette smoking has been linked with the upregulation of angiotensin-converting enzyme-2 in lung cells ( 55 , 56 ) and weakened immune system ( 57 ); it was also reported that patients with smoking history were associated with more progressed COVID-19 symptoms ( 58 ). Moreover, cigarette smoking has been linked to aggravating neuropsychiatric symptoms, systemic inflammation, coagulation, and other clinical symptoms in COVID-19 patients through nicotine and nicotinic-cholinergic system interaction ( 59 , 60 ). The rising cigarette consumption in some respondents might be driven by factors other than psychopathologies, as neither significant difference in SCL-90 scores nor correlation in the regression analysis were seen.…”
Section: Discussionmentioning
confidence: 99%
“…Especially during this pandemic, cigarette smoking has been linked with the upregulation of angiotensin-converting enzyme-2 in lung cells ( 55 , 56 ) and weakened immune system ( 57 ); it was also reported that patients with smoking history were associated with more progressed COVID-19 symptoms ( 58 ). Moreover, cigarette smoking has been linked to aggravating neuropsychiatric symptoms, systemic inflammation, coagulation, and other clinical symptoms in COVID-19 patients through nicotine and nicotinic-cholinergic system interaction ( 59 , 60 ). The rising cigarette consumption in some respondents might be driven by factors other than psychopathologies, as neither significant difference in SCL-90 scores nor correlation in the regression analysis were seen.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be considered that current smokers cease to be so when entering the hospital, as far as nicotine is concerned. In our work, we only refer to the fact that there are less hospitalised current smokers than expected, which is why nicotine has been suggested to very likely have a protective effect against serious symptoms, calming the cytokine storm (see Section 4.2, [36,38,43]). This might be a cause of underrepresentation among hospitalised patients.…”
Section: Limitations and Biasesmentioning
confidence: 99%
“…Most of them have been systematic reviews and meta-analyses focusing on the association between smoking, disease progression and severity of the outcomes for COVID-19 patients (largely showing a positive relation between these factors) [8,12,14,[24][25][26][27][28][29][30][31][32][33][34][35]. However, to the best of our knowledge, just a few works have focused on studying the low prevalence of current smokers within hospitalised COVID-19 patients-mainly found in clinical data from China outbreak reports or early USA data-and more importantly, proposing potential pathophysiological explanations for these findings [36][37][38][39][40][41][42][43]. In this sense, nicotine or nicotinic receptor agonists were early proposed as plausible anti-inflammatory mediators acting on the immune system to counteract the "cytokine storm" found in severe SARS-CoV-2 infected patients [43].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would seem that smokers should be at an increased risk of both contracting COVID-19 and developing severe infection ( 7 ). The data have been mixed, with most studies suggesting that active smoking may predispose to infection and progression to severe disease ( 8 , 9 ) but a few studies (some unreviewed) suggesting that smokers may be protected from getting COVID-19 ( 10 12 ). However, nicotine itself has also been (separately) proposed as a potential therapeutic agent in COVID-19 because of its activation of nicotinic cholinergic receptors ( 8 ).…”
mentioning
confidence: 99%